Security strategy under uncertainty : understanding Malaysia’s strategic behaviour in East Asian power shifts - Chua, Pei Qi (Nanyang Technological University, 2020)
The emergence of China as a rising power has posed as a threat to U.S. dominance, resulting in the return of balance of power politics whereby relations between China and the U.S. are increasingly characterised by rivalry and conflicts. Against this backdrop, East Asia is faced with uncertainties arising from power shifts. As traditional balance of power theory lacks a consensus on secondary states’ strategic behaviour, this paper seeks to develop an understanding of the conditions which underlie secondary states’ strategic behaviours in times of power shifts. Through the examination of Malaysia as a case study, this paper looks at Malaysia’s perceptions of major powers’ behaviours over three periods of power shifts, and the extent to which these perceptions inform its strategic behaviour. This paper finds that perceptions are useful insofar that it explains the type of strategic behaviour adopted. Nonetheless, it is limited in explaining the extent to which Malaysia practices such strategic behaviours.